OPTIMIZING FAMILY RESILIENCE TO PREVENT STUNTING DURING THE COVID-19 PANDEMIC - Marlina, Asti; Gatot, Masitowati (LPPM Univ. Ibn Khaldun Bogor, 2023)
The Covid-19 pandemic has drastically changed the order of our lives in various aspects. One of the significant impacts is the increased risk of stunting in children. Stunting is a condition of failure to thrive caused by malnutrition and lack of nutrients over a long period of time. Children who are stunted have a shorter height than other children of their age and tend to experience delays in physical and mental development. Stunting can have a long-term impact on a child's quality of life, including problems with health, education and future productivity. Family resilience has a central role in preventing stunting in children. In the COVID-19 pandemic situation, an appropriate strategy is needed to reduce the occurrence of stunting, especially in CIjujung village, Sukaraja sub-district, Bogor Regency. The strategies are increasing access to nutritious food and providing training on how to generate additional income so that fulfillment of nutritious food can still be carried out, education on nutrition, good sanitation, routine health checks, exclusive breastfeeding and social support can help families prevent stunting in pandemic period. Thus, the role of the family in providing adequate nutrition and supporting the growth and development of children is very important in maintaining a healthy and strong generation in the future.